[(η3-Bi3)2(IrCO)6(μ4-Bi)3]3−: a new archetype of a 15-vertex deltahedral hybrid from Bixx−-coordination aggregation of cationic [IrCO]+ units. Issue 32 (23rd July 2019) - Li, Zhenyu; Liu, Caiping; Wu, Jie; Lin, Zian; Xu, Li
Abstract : The first Zintl-deltahedral metal carbonyl hybrid [(η 3 -Bi3 )2 (IrCO)6 (μ4 -Bi)3 ] 3− was obtained by a new synthetic methodology, namely the Bi x x − -coordination aggregation of [Ir(CO)] + to trigonal prismatic [Ir(CO)]6 6+ . Abstract : The reaction of Ir(CO)2 (acac) (acac = acetylacetonate) and K5 Bi4 in ethylenediamine (en) solution produces a new archetype of a 15-vertex deltahedral hybrid, [(η 3 -Bi3 )2 (IrCO)6 (μ4 -Bi)3 ] 3− (1a ), from the Bi x x − -coordination aggregation of the [Ir(CO)] + cationic units, providing a feasible route towards new hybrid compounds made by the combination of Zintl anions and transition-metal carbonyl clusters.